Advertisement Remove all ads

D Y D X − Y Cot X = C O S E C X - Mathematics

Sum

\[\frac{dy}{dx} - y \cot x = cosec\ x\]

Advertisement Remove all ads

Solution

We have,

\[\frac{dy}{dx} - y \cot x = cosec\ x\]

\[\text{Comparing with }\frac{dy}{dx} + Py = Q,\text{ we get}\]

\[P = - \cot x \]

\[Q = cosec\ x\]

Now,

\[I . F . = e^{\int - \cot x\ dx} \]

\[ = e^{- \log \left| \left( \sin x \right) \right|} \]

\[ = e^{\log \left| \left(cosec\ x \right) \right|} \]

\[ = cosec x\]

So, the solution is given by

\[y\ cosec\ x = \int cosec\ x \times cosec\ x\ dx + C\]

\[ \Rightarrow y\ cosec\ x = \int {cosec}^2 x dx + C\]

\[ \Rightarrow y\ cosec\ x = - \cot x + C\]

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 12 Maths
Chapter 22 Differential Equations
Revision Exercise | Q 40 | Page 146
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×